دور دراسة علم المعاني لدى طلاب مستوى ثاني الكلية في فهم الأساليب البلاغية في سورة آل عمران الأمر نموذجاً - Rahmat Sapaat; Abd. Rohim (Rayah Al-Islam, 2018)
The study aims to analyze Students skill level of second semester of STIBA Ar-Raayah in understanding Asãlîb al-Amr and the meaning in al-Quran, and analyze how far the role of learning Al-Ma’ãnî towards students in understanding Al- Asãlîb Al- Balãghiyyah in al-Quran. From the result of test that is conducted, obtained the research results as follows: 1) In surah Ali Imron there are 56 verses contain the number of amr that is 78 numbers, 36 numbers show the meaning of amr hakiki and 51 number show the meaning of amr majazi, 2) A study of Al-Ma’ãnî has a major role towards the students of second semester STIBA AR-Raayah in understanding Al-Asãlîb Al-Balãghiyyah in al-Quran. It is obtained from the test result where 74,4% of students can comprehend and answer correctly the meanings of Amr that are contained in some verses which have applied the test to them, that proportionate with 25,6% of students who do not answer correctly. 3) The researcher finds some ways to increase the skill level of students in understanding Al-Asãlîb Al-Balãghiyyah in al-Quran, including by increasing the example from al-Quran verse with the interpretation, and by increasing more practice with various methods.